Analisis Kemampuan Berbahasa Dan Perilaku Moral Pada Anak Usia Dini Di Masa Pandemi Melalui Metode Bercerita - Siti Nurjanah; Machmudah Machmudah; Nurul Kamariyah; Chilyatiz Zahroh; Nur Ainiyah (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
Abstract The ocvid-19 pandemic period caused the Minister of Education and Culture to work to carry out online learning (distance) which applies from early childhood learning to higher education. Online learning uses gadgets that are under the supervision of parents, many parents are impatient in assisting early childhood in learning. This causes parents to often get angry by saying rude things to their children. Early childhood needs role models, namely to teach language and good morals from an early age.The purpose of this study was to assess language skills and moral behavior in early childhood using the storytelling method (hand puppets and picture series). This research method is correlative analytic with cross sectional approach. The population in this study were students at PPT Sawahan. The number of samples is 65 children. The sampling technique used was consecutive sampling. The dependent variable in this study is the Storytelling Method. The independent variables are language skills and moral behavior. The instruments used in this study were hand puppets to tell stories, serial cards, while to measure language skills and moral behavior (polite, honest, responsible) using indicators in early childhood education, measured based on observations or observations. The results of the study after being given the method for six meetings with large language interactions (53.85%) developed as expected. Most of the moral behavior (polite, honest, responsible) (61.54%) developed very well. The use of storytelling methods during learning at an early age can improve children's language skills and moral behavior.